Dogs' behavioural responses to repeated positive events - Westerback, Therese (2011)
Assessing the emotional state in animals is important in order to establish the quality of their welfare, therefore it is important to investigate under what circumstances animals experience these emotions and to find indicators of their existence. The aim of this thesis was to detect possible behavioural indicators for positive emotions in dogs. These behavioural indicators could be helpful to increase both dogs’ and humans’ overall well-being in today’s society since they could help e.g. dog owners and caretakers to interpret behaviours displayed by dogs and their intentions so they can respond accordingly.